Oxidation and tensile behavior of ferritic/martensitic steels after exposure to lead-bismuth eutectic - Liu, Jian; Shi, Quanqiang; Luan, He; Yan, Wei; Sha, Wei; Wang, Wei; Shan, Yiyin; Yang, Ke (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2016)
Two ferritic/martensitic steels, T91 steel and newly developed SIMP steel, were subject to tensile test after being oxidized in the liquid lead-bismuth eutectic (LBE) at 873K for 500h, 1000h and 2000h. Tensile tests were also carried out on the steels only thermally aged at 873K. The result shows that thermal aging has no effect. Exposure to LBE at 873K leads to a slight decrease in strength, but a large decrease in elongation when tested at 873K. When tested at 873K after 2000h exposure, the tensile strength of T91 decreases slightly, and elongation from 39% to 21%. For SIMP, the decreases are slightly and from 44% to 28%, for tensile strength and elongation, respectively. The room temperature strength has slightly larger percentage reductions after the LBE exposure, but the elongation changes little.